Oligodendrogenesis after cerebral ischemia - Zhang, Ruilan; Chopp, Michael; Zhang, Zheng Gang (Frontiers in Cellular Neuroscience, 2013)
Abstract Neural stem cells in the subventricular zone (SVZ) of the lateral ventricle of adult rodent brain generate oligodendrocyte progenitor cells (OPCs) that disperse throughout the corpus callosum and striatum where some of OPCs differentiate into mature oligodendrocytes. Studies in animal models of stroke demonstrate that cerebral ischemia induces oligodendrogenesis during brain repair processes. This article will review evidence of stroke-induced proliferation and differentiation of OPCs that are either resident in white matter or are derived from SVZ neural progenitor cells and of therapies that amplify endogenous oligodendrogenesis in ischemic brain.